Enhancing Social Networking Learning by Using Enterprise Social Networks - Ramona-Diana Leon; Rauĺ Rodriǵuez-Rodriǵuez; Alfaro-Saiz (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2023)
Social networking learning is emerging in light of the European Skills Agenda and technological development. This aims to incorporate learning techniques in social networking environments to foster formal and informal learning. However, the classical customer-oriented social networks provide an essential learning environment that does not include assessment tools and pedagogical perspectives. The enterprise social networks could fill this gap since they are more flexible, easy to customise, and highly efficient in the organisational learning context. This research, with its practical implications, aims to bring forward the enterprise social networks that can answer higher education demands and the selection criteria that could be considered. An emic approach is employed, and a conceptual design is developed. The results present a multi-criteria decision model that can be used by higher education teachers who want to move forward to social networking learning. The current approach has theoretical and practical implications; it extends the literature on educational technologies and helps teachers decide which enterprise social network they can use in their activities.
Keywords: O32; O33; A23; I23; 330; enterprise social network; higher education institution; students; knowledge sharing; informal learning